Prevalence, Incidence and Mortality Rates of Cervical Cancer in India: based on Global Burden - Gupta, Seema (Journal of Neonatal Surgery, 2025)
Background: According to the latest GLOBOCAN statistics, cervical cancer ranks as the fourth most common cancer in terms of incidence and mortality among women worldwide, following only breast cancer, colorectal cancer, and lung cancer. In low-income countries, cervical cancer is the second most common fatal malignant tumor . Evidently, cervical cancer causes a substantial burden on women’s public health globally. Cervical cancer incidence and mortality rates in the United States have substantially declined over recent decades, primarily driven by reductions in squamous cell carcinoma cases. However, the trend in recent years remains unclear. This study was aimed to explore the trends in cervical cancer incidence, prevalence and mortality, stratified by demographic, particularly age- related incidence, death rates, rural and urban population, screening programme and tumor characteristics from 2000 to 2030 in India, in Global context. Among the selected countries, India exhibited the lowest incidence and mortality rates for all-cause cancer among women, with rates of 100.83 and 62.61 per 100,000 person-years, respectively. However, the ASIR and ASMR of cervical cancer were the second highest in India (17.71 and 11.15 per 100,000 person-years) after South Africa (33.18 and 19.03 per 100,000 person-years). The incidence rates in India are below the global median for all cancers (157.66), breast cancer (46.21), and corpus uteri cancer (7.03), but they are above the global median for cervix uteri cancer (14.10). A similar trend was observed concerning cancer-related mortality rates among Indian women. Nearly 54% of cancer incidence and 50% of cancer mortality among women in India are attributed to these six female-specific cancers. Conclusions: India contributed significantly to the global burden of female-specific cancers, the ASIR and ASMR for these cancers were lower than those in many other countries. It was essential to study how sociodemographic transitions influenced the patterns of female-specific cervical cancer in high, low, and middle-income countries to inform the implementation of effective cancer control strategies by health systems in India as compared to other countries.